Tradução e adaptação transcultural do instrumento de transtornos alimentares : Eating Disorder Examination Questionnaire Short (EDE-QS) - Pedrosa, Maria Amália Accari (2024)
Eating disorders (ED) are conditions that represent a great impairment in the quality of life of the subject, both due to psychosocial repercussions and associated clinical complications. Primary Health Care (PHC) is an important mental health care center of the Psychosocial Care Network (RAPS) of the Brazilian Unified Health System (SUS), where comprehensive and longitudinal care of the user is recommended. However, in the context of ED, the international literature points out some difficulties related to primary care, such as: low recognition of symptoms, either due to the knowledge of professionals or due to the user's resistance to seeking help, late diagnosis in the face of complications, insecurity in management due to the complexity of the conditions, however, studies show that training and the provision of professional tools help in the diagnosis and coordination of the Care. Brazil is a continental country, considered to be middle-income, but with significant social inequality and access to care, including health, therefore, a clinical review of the instruments available for ED screening in PHC was carried out, considering the particularities of care in our country. In view of the search and critical analysis, an instrument with the desired characteristics was identified: application by the non specialist, fast and practical, good discriminatory power, record of applicability in different samples. Thus, the objective of this study was to translate and cross culturally adapt the EDE-QS "Eating Disorder Examination Questionnaire Short (EDE-QS)". A semantic equivalence study was carried out, based on the following steps: 1: translation by two bilingual translators with Portuguese mother tongue, 2: reconciliation between the versions by a third translator, 3: reverse translation of the final preliminary version 4: validation and reconciliation of the back translation by the original authors, 5: cultural validation of the final version of the translation by a panel of six experts 6: Pre-test in a non-clinical sample to assess the understanding of the questions; and, finally, the elaboration of the final version of the instrument The above translation steps were completed according to the protocol described. In the analysis of content validity by experts, equivalences were analyzed at the item and scale level, and S-CVI was reached: 0.93 (semantics), 0.98 (idiomatic), 0.98 (experiential), 0.98 (conceptual) (minimum acceptable of 0.83). In the comprehension assessment, all items received more than 80% of understanding, and the application time was approximately 10 minutes. The Portuguese version of the EDE-QS showed adequate semantic equivalence compared to the original. In the target population, it demonstrated good verbal comprehension and practicality related to the time of application. The availability of tools with applicability in PHC is extremely relevant for early diagnosis and coordination of levels of care, thus enabling comprehensive care for users in line with SUS principles.